Islamic Republic of Afghanistan : Fourth Review Under the Extended Credit Facility Arrangement, Request for Modification of Performance Criteria, and Request for Extension and Rephasing of the Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
Background: The three-year arrangement under the Extended Credit Facility (ECF) for SDR 32.38 million (USD 44.9 million, or 10 percent of quota) was approved on July 20, 2016. The first three reviews under the ECF were completed in May 2017, December 2017, and May 2018. The arrangement supports the government's reform agenda-as outlined in the Afghanistan National Peace and Development Framework (ANPDF)-to lay the foundation for higher growth and job creation and aims to catalyze continued support from donors. Context: Violence swelled ahead of and during the October 20 parliamentary elections, but voter turnout was relatively strong despite severe operational challenges. Peace efforts have intensified, with the participation of the United States and regional powers. The poor security situation and electoral year uncertainties are undermining confidence and growth, and present risks to program implementation. A key focal point for this year is the Geneva Ministerial Conference on Afghanistan taking place on November 27-28, 2018. The conference aims to review reform progress, showcase the National Unity Government's achievements, and secure continued donor support.